Linking air stagnation in Europe with the synoptic- to large-scale atmospheric circulation - Maddison, Jacob William; Ábalos Álvarez, Marta; Barriopedro Cepero, David; García Herrera, Ricardo Francisco; Garrido Pérez, José Manuel; Ordóñez García, Carlos (Weather and Climate Dynamics, 2021)
The build-up of pollutants to harmful levels can occur when meteorological conditions favour their production or accumulation near the surface. Such conditions can arise when a region experiences air stagnation. The link between European air stagnation, air pollution and the synoptic- to large-scale circulation is investigated in this article across all seasons and the 1979–2018 period. Dynamical indices identifying atmospheric blocking, Rossby wave breaking, subtropical ridges, and the North Atlantic eddy-driven and subtropical jets are used to describe the synoptic- to large-scale circulation as predictors in statistical models of air stagnation and pollutant variability. It is found that the large-scale circulation can explain approximately 60 % of the variance in monthly air stagnation, ozone and wintertime particulate matter (PM) in five distinct regions within Europe. The variance explained by the model does not vary strongly across regions and seasons, apart from for PM when the skill is highest in winter. However, the dynamical indices most related to air stagnation do depend on region and season. The blocking and Rossby wave breaking predictors tend to be the most important for describing air stagnation and pollutant variability in northern regions, whereas ridges and the subtropical jet are more important to the south. The demonstrated correspondence between air stagnation, pollution and the large-scale circulation can be used to assess the representation of stagnation in climate models, which is key for understanding how air stagnation and its associated climatic impacts may change in the future. Ministerio de Economía, Comercio y Empresa (España) Ministerio de Ciencia, Innovación y Universidades (España) Ministerio de Educación, Formación Profesional y Deportes (España) Comunidad de Madrid Depto. de Física de la Tierra y Astrofísica Fac. de Ciencias Físicas TRUE pub